THE EFFECTIVENESS OF E-OFFICE IN IMPROVING ADMINISTRATIVE GOVERNANCE: A CASE STUDY AT SURABAYA STATE UNIVERSITY - Muhammad Afif Maulana Hidayat; Triesninda Pahlevi (SYNTIFIC, 2026)
Background. Implementation of E-Office systems has become an important strategy in supporting digital transformation within higher education institutions to improve the effectiveness of administrative governance and support more efficient organizational performance. Research Purpose. This study aimed to analyze the effectiveness of E-Office system implementation in improving administrative governance at Universitas Negeri Surabaya by emphasizing the interaction among technological factors, human resources, and organizational context. Research Method. This study employed a qualitative approach with a case study design. Data were collected through semi structured interviews with five key informants consisting of a system administrator, an E-Office operator, administrative staff members, and a structural official directly involved in the implementation and use of the E-Office system. The study was supported by the analysis of institutional documents and regulations related to official correspondence administration and electronic records management. Data were analyzed using thematic analysis assisted by NVivo 15 to identify major patterns and themes. Findings. The implementation of E-Office has improved administrative efficiency through faster document distribution, reduced paper usage, enhanced transparency through document tracking features, and facilitated digital records management. However, the implementation still faces several challenges, including differences in users’ digital competencies, the need for continuous training, and the persistence of several administrative processes that are still conducted manually. Conclusion. The effectiveness of E-Office implementation is determined not only by the quality of the technology but also by the readiness of human resources, organizational support, and the alignment of the system with organizational work practices.